Fluoretação da água no Brasil: distribuição regional e acurácia das informações sobre vigilância em municípios com mais de 50 mil habitantes - COSTA, Angelo Giuseppe Roncalli da (Fundação Oswaldo Cruz, 2019)
Sanitation data for 2008 indicated that 74.4% of Brazilian municipalities (counties) with more than 50,000 inhabitants were receiving fluoridated water, but no criteria were adopted to validate the information. The study aimed to verify the accuracy of information on water fluoridation, using as the reference water surveillance data from municipalities with more than 50,000 inhabitants in 2008 and during 2010-2015. Data from different sources were used, comparing the information pertaining to the period. Water samples were collected, and fluoride concentration was obtained by the electrometric method. Verification was performed by comparing the data obtained from different sources. Data were compared for 601 (97.9%) municipalities. The proportion of municipalities that performed surveillance based on external control increased from 39.4% to 48.5%. There was a high rate of false positives and false negatives (15.1%) in the data for 2008. Municipal coverage was 70.2%, or 4.2 percentage points below the published estimate (74.4%) for 2008. Surveillance records were observed in 54.3% of the fluoridated municipalities whose population coverage reached at least 50% of the population receiving treated water. There was an important improvement in fluoridation surveillance data, despite a high percentage of false positives and negatives. There are still wide interregional differences in the surveillance of water fluoridation in this sample of Brazilian municipalities, raising important public health challenges.